Design process for mechanism for coffee harvesting (2017)
The main objective of this project was to use a design method based on a mechatronic approach in order to develop a prototype of a Coffee fruit harvester for the Colombian and similar coffee fields. Different areas were analyzed, such as mechanical, electrical and software domains. A prototype was achieved, but ended with some flaws due to some manufacturing processes. The purpose of the project was to create a prototype and was NOT to achieve a final commercial product